A case−control study of elective hip surgery among HIV‐infected patients: exposure to systemic glucocorticoids significantly increases the risk. Issue 3 (11th September 2013) - Kerr, E; Middleton, A; Churchill, D; Reading, I; Walker‐Bone, K
<x xml:space="preserve">Abstract</x> Objectives This was a cross‐sectional study with a nested case−control analysis among a cohort of HIV‐infected adults aiming to explore the prevalence of and risk factors for elective hip surgery (total hip arthroplasty and resurfacing). Methods Cases were identified from the out‐patient database of HIV‐infected adults attending one tertiary hospital service. For each case, five controls from the same database matched by age, gender and ethnicity were identified. From the case notes, information about demographic factors, HIV factors and risk factors for hip surgery attributable to osteoarthritis or avascular necrosis (body mass index, lipids, alcohol, comorbidities and treatment with oral glucocorticoids) was extracted. Results Among the cohort of 1900 HIV‐infected out‐patients, 13 cases (12 male) who had undergone hip surgery [0.7%; 95% confidence interval (CI) 0.3−1.1%] were identified, with a median age of 47 years. Eleven of the 13 cases (85%) were Caucasian and seven of the 13 were in stage 3 of HIV infection. Fewer of the cases were in the asymptomatic stage of infection compared with controls [odds ratio (OR) for stage 2 or 3 infection 4.0; 95% CI 0.8–18.5]. Ever having used oral glucocorticoids was highly significantly associated with elective hip surgery (OR 44.6; 95% CI 5.7–347.7). Conclusions Among this young cohort, the prevalence of elective hip surgery was 0.7%, with the median age at surgery being 47 years. Ever having been exposed to systemic glucocorticoids was highly significantly associated with elective hip surgery, suggesting that the principal mechanism underlying the need for surgery was avascular necrosis. There may be an increased need for elective hip surgery associated with HIV infection.